Pollen morphology of selected melliferous plants and its taxonomic implications using microscopy - Attique, R. (John Wiley and Sons Inc, 2022)
This research aimed to explore the melliferous bee flora pollen from arid zones of District Attock, Islamabad Capital and Rawalpindi. Morpho-palynological features has provided key information for the classification and help to explain the taxonomy of several genera and species. Therefore, in this work, we examined the morphological characters of pollen potentially to be used for the species delimitation of bee flora. A total of 18 bee floral species, classified into 12 different families were collected, pressed, identified and then acetolyized to observe the grains under microscopy. Bee pollen can be described by small, medium to large sized morphotypes presenting five types of shapes, prolate spheroidal in (seven species), sub-prolate (six species), oblate spheroidal (three species), oblate and prolate (one species each) was examined. The observed polar and equatorial diameter were found maximum in Zea mays 73.5Â Î¼m and Pelargonium inquinans 66.75Â Î¼m respectively. Pollen of six different types was found namely: tricolporate, 3-zonocolporate, monoportae, tetracolporate, tetraporate and mononsulcate. Whereas highest value of colpi length was measured in Grewia tenax (24.55Â Î¼m). Exine surface nature of pollen was examined echinate psilate and scabrate. Exine thickness noted to be maximum in Verbena tenuisecta (8.40Â Î¼m) and minimum in Citrus macrocarpa (0.4Â Î¼m). Bee floral species considered difficult to identify based on other morphological traits were successfully distinguished using pollen quantitative and qualitative traits, confirming the importance of pollen morphology to diagnose characters to correctly identify honeybee flora. Â© 2022 Wiley Periodicals LLC.